Gambaran Faktor Penyebab Stunting Pada Balitas di Desa Mranggen Kecamatan Polokarto Kabupaten Sukoharjo - Aditiya, Siska; Drajad Pamukhti, Bagas Biyanzah (Jurnal Pakar Kesehatan, 2025)
Stunting is one of the major nutritional problems that has become a global concern. In 2024, there were 4,113 cases of stunting among toddlers in Sukoharjo, accounting for 9.42%. The highest number of stunting cases among toddlers was recorded at the Polokarto Public Health Center, with 640 cases, where Mranggen Village contributed 80 cases in 2025. Objective: To determine the description of factors causing stunting among toddlers in Mranggen Village, Polokarto Subdistrict, Sukoharjo Regency. Method: This study used a descriptive quantitative design with a total sampling technique involving 80 mothers of stunted toddlers as respondents. Data were collected using a questionnaire and analyzed through frequency distribution. Results: The results show that the majority of respondents were aged 20–35 years, totaling 59 respondents (73.8%). Most of the mothers were housewives, amounting to 58 respondents (72.5%). The majority of infants had a birth weight  ≥ 2500 grams, with 70 respondents (87.5%). Respondents with an income below the regional minimum wage (Rp. 2,359,488.00) totaled 59 respondents (73.8%). Mothers who provided exclusive breastfeeding for six full months were 52 respondents (65.0%). In terms of education, most mothers had completed senior high school, totaling 50 respondents (62.5%). Meanwhile, the level of knowledge was categorized as good in 26 respondents (32.5%), moderate in 38 respondents (47.5%), and poor in 16 respondents (20.0%). Conclusion: The factors influencing stunting among toddlers in Mranggen Village, Polokarto District, Sukoharjo Regency include maternal age, occupation, birth weight (BBL), income, exclusive breastfeeding, education, and maternal knowledge. Nutritional education and economic support need to be strengthened to reduce the prevalence of stunting.